Morphological drivers of trophic cascades. Issue 8 (22nd December 2015) - Renneville, Clémentine; Rouzic, Arnaud Le; Baylac, Michel; Millot, Alexis; Loisel, Stéphane; Edeline, Eric
Abstract : Worldwide, local anthropogenic extinctions have recently been reported to induce trophic cascades, defined as perturbations of top consumers that propagate along food chains down to primary producers. This focus on the effects of top‐consumer extinction (i.e. of species presence) ignores potential cascading effects of the rapid morphological changes that may precede extinction. Here, we show in an experimental, three‐level food chain including medaka fish, herbivorous zooplankton and unicellular algae that varying body length of a single fish from large (36.3 mm) to small (11.5 mm) induced a stronger trophic cascade than varying an average‐sized (23.8 mm) fish from being present to absent. The strength of fish predation on zooplankton scaled quasi linearly (not with a power exponent) with fish body length and associated gape width, suggesting that the resultant trophic cascade was morphology (not metabolism)‐dependent. The effect of fish body length was stronger on phyto‐ than on zooplankton, because large‐sized fish had the unique ability to suppress large‐sized herbivores, which in turn had high grazing capacities. Hence, our results show that consumer body size, by setting diet breadth, can both drive and magnify the strength of trophic cascades. In contrast, fish body shape had no significant effect on fish predatory performances when its allometric component (the effect of size on shape) was removed. In the wild, human‐induced body downsizing of top consumers is widespread, and mitigating the resultant perturbations to ecosystem function and services will require a paradigm shift from preserving species presence towards preserving species size structure.